2009
DOI: 10.1089/ees.2007.0186
|View full text |Cite
|
Sign up to set email alerts
|

Storm Water Runoff Mitigation Using a Green Roof

Abstract: A prototype green roof was constructed and monitored in Pittsburgh, Pennsylvania, to demonstrate a way to reduce storm water runoff and combined sewer overflow (CSO) events. The large impervious surface area created by urban development in Pittsburgh creates a wet weather flow that the existing combined waste waster and storm water sewer system cannot contend with. Green or vegetated roofs can reduce the amount of storm water that reaches the sewer conveyance system by replacing an otherwise impervious roof wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(76 citation statements)
references
References 1 publication
5
63
0
8
Order By: Relevance
“…In addition, there are many advantages for the environment, ranging from increasing the thermal insulation of the building envelope and reduction of urban heat island effects [127][128][129][130][131][132][133][134][135], acting as a buffer for storm water [135][136][137][138][139][140], improving air quality and increased carbon-dioxide uptake [141][142][143], increasing urban biodiversity [144][145][146][147], providing a visually pleasant environment [148], to even crop harvesting. Also from an economical point of view, building greening seems interesting [149][150][151][152].…”
Section: Ground Treatmentmentioning
confidence: 99%
“…In addition, there are many advantages for the environment, ranging from increasing the thermal insulation of the building envelope and reduction of urban heat island effects [127][128][129][130][131][132][133][134][135], acting as a buffer for storm water [135][136][137][138][139][140], improving air quality and increased carbon-dioxide uptake [141][142][143], increasing urban biodiversity [144][145][146][147], providing a visually pleasant environment [148], to even crop harvesting. Also from an economical point of view, building greening seems interesting [149][150][151][152].…”
Section: Ground Treatmentmentioning
confidence: 99%
“…Moran et al (2005) observed the substantial release of TN from green roofs. Bliss et al (2009) showed the COD of green roof water samples was greater than those from a control roof (conventional ballasted membrane roof), and Mason et al (1999) found that the roof runoff infiltration through soil showed that a major part of DOC behaved conservatively during infiltration. Therefore, the green roof was not suitable for rainwater harvesting applications.…”
Section: Effect Of Different Roofing Materials On Harvested Rainwatermentioning
confidence: 99%
“…Rain samples are slightly acidic, with a pH between 6 and 7. It appears that green roofs have the effect of mitigating mild acid rain [26].…”
Section: Storm Water Qualitymentioning
confidence: 99%